Problems of protection of the rights to real estate in modern armed conflicts - Spiesivtsev, Denys (Fundacja "Ośrodek Rozwoju Kompetencji Akademickich", 2023)
The article is devoted to the consideration of the modern challenges for the doctrine of grounds for protection of rights to real estate in the context of modern armed conflicts. The author define factors that determine necessity of modernization of current legal mechanism of property rights protection and considers two main models of violation property rights to real estate during armed conflict: 1) armed groups carry out shelling of objects of real estate that are private property; 2) armed groups establish control over certain objects of real estate that are private property and use them to arrange fire positions in connection with which they are attacked by government forces. Turning to provisions of Ukrainian legislation and international conventions he describes main possible means of restoration property rights to real estate that were violated during armed conflict. Main provisions of effective control doctrine are considered. Features of doctrine of protection and self-defense are formulated.
Keywords: Civil law; real estate; immovable property; protection of civil rights; property rights; armed conflict; self-defense; non-state actors